The Role of Big Data Analytics in the Relationship among the Collaboration Types, Supply Chain Management and Market Performance of Thai Manufacturing Firms - Tippawan Chakphet; Mallika Saenpakdee; Thaniya Pongsiri; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2020)
The current study is carried out to explore role of big data analytics in the relationship among the collaboration types, supply chain management and market performance of Thai manufacturing firms. It has been revealed through literature review that collaboration among the firms is more than just coordination. It is referred as inter-firm interaction with key focus on strategies. This type of collaboration can be witnessed in two different ways, which include STRC and SYSCL [1] . The concepts of STRC and SYSCL have not been recognized separately in literature as they create difference influences on the performance of firm. The study has employed the SEM-PLS to analyze the data. The study broached an argument that the system collaboration includes coordination, sharing of information, and activities management for planning and forecasting of demand. The next level of inter-firm interaction is the STRC. In this advanced level, achievements are more than just SYSCL. The level with which the partners in supply chain plan different business activities with the shared vision to improve the performance of each other is referred as STRC.